BENTUK PENYAJIAN GENDANG SERUNAI DALAM UPACARA PESTA PERKAWINAN DI SUNGAI GUNTUNG KECAMATAN KATEMAN KABUPATEN INDRAGIRI HILIR - Prayuni Amanda Putri; Wimbrayardi Wimbrayardi; Yos Sudarman (SENDRATASIK UNP, 2018)
AbstrakThis reseach aims at finding out and describe about “Gendang Serunai” in wedding ceremonies at Sungai Guntung, Indragiri Hilir. This qualitative research applied the descriptive analysis method.  The object was the performing art of “Gendang Serunai”.  Data were obtained from library study, observation, interview, and documentation.  They were later analyzed qualitatively.The research result shows that “Gendang Serunaiis performed as a collaboretive ensamble of Gendang Serunai, and Gong.  It is also accompanied with ythe performances of martial art and the “Inai Dance”.  During the performance, the players of Gendang sit face to face.  The Serunai player sits at the back of ythe Gendang Jantan player and the Gong player sits at the back of the Gendang Betina players.  There are two processions of “Gendang Serunai” in wedding ceremonies.  The first in as an opening performance with the martial are while the second one is as the main performance with gthe dance.  “Gendang Serunai” is usually performed at wedding and welcoming ceremonies. Keywords: Bentuk Presentation Form, Drums, Wedding Ceremonies